2007
DOI: 10.2478/v10004-007-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Liver and Brain Cytochrome P450 after Multiple Cocaine Administration, Alone and in Combination with Nifedipine

Abstract: The objective of this study was to evaluate possible changes caused by multiple cocaine administration, alone and in combination with 1,4-dihydropiridine calcium channel blocker nifedipine, on cytochrome P450 levels both in the brain and liver. The experiment was done on male Wistar rats divided in four groups: control, treated with nifedipine (5 mg kg -1 i.p. for five days), treated with cocaine (15 mg kg -1 i.p. for five days), and treated with nifedipine and 30 minutes later with cocaine (also for five days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Nifedipine given alone showed the opposite effects to cocaine, signifi cantly increasing cytochrome P450 quantity (28 %) and ethylmorphine-N-demethylase (34 %) and anilinehydroxylase (27 %) activity in respect to control. These results are in good correlation with our earlier fi ndings (5,12).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Nifedipine given alone showed the opposite effects to cocaine, signifi cantly increasing cytochrome P450 quantity (28 %) and ethylmorphine-N-demethylase (34 %) and anilinehydroxylase (27 %) activity in respect to control. These results are in good correlation with our earlier fi ndings (5,12).…”
Section: Discussionsupporting
confidence: 82%
“…In our earlier studies, we investigated the effect of cocaine on brain and liver cytochrome P450 after multiple administration in rats and found that the cumulative intraperitoneal (i.p.) dose of 15 mg kg -1 led to a signifi cant increase in the quantity of cytochrome P450 (12) and in ethylmorphine-N-demethylase (CYP 3A) (13) and anilinehydroxylase (CYP 2E1) activity (14). These fi ndings suggest that cocaine and nifedipine interact in the brain and liver.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, Vitcheva and Mitcheva (2007) found that cocaine treatment significantly decreased P450 in the liver by 17% as compared with controls, suggesting that cocaine may affect serum testosterone levels. Although it is not clear how cocaine affects liver function in adolescent rats, differences in serum testosterone levels between saline- and cocaine-treated adolescent rats may in part be due to cocaine’s effects on liver enzymes.…”
Section: Discussionmentioning
confidence: 97%